2008
DOI: 10.3155/1047-3289.58.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distributions and Elemental Composition of Atmospheric Particulate Matter in Southern Italy

Abstract: Three 2-wk seasonal field campaigns were performed in 2003 and 2004 at a sampling site on the southern Tyrrhenian coast of Italy with the aim to investigate the dynamics and characteristics of particle-bound pollutants in the Mediterranean area. Fine (PM 2.5 ) and coarse particulate matter (PM 10 -2.5 ) size fractions were collected by a manual dichotomous sampler on 37-mm Teflon filters over a 24-hr sampling period. On average, 70% of the total PM 10 (PM 2.5 ϩ PM 10 -2.5 ) mass was associated with the coarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Possible sources of crustal material within the basin included dust from paved highways and roads, unpaved roads, agricultural fields, arid desert land, earth moving, plowing or harvesting activities, and mining. This is consistent with current knowledge of PMc sources (Sprovieri and Pirrone, 2008;Begum et al, 2010;Cheung et al, 2012;Kassomenos et al, 2012;Kumar et al, 2012). Many of these sources can contribute to particle entrainment of soil-related material into the atmosphere during monsoon wind events.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Possible sources of crustal material within the basin included dust from paved highways and roads, unpaved roads, agricultural fields, arid desert land, earth moving, plowing or harvesting activities, and mining. This is consistent with current knowledge of PMc sources (Sprovieri and Pirrone, 2008;Begum et al, 2010;Cheung et al, 2012;Kassomenos et al, 2012;Kumar et al, 2012). Many of these sources can contribute to particle entrainment of soil-related material into the atmosphere during monsoon wind events.…”
Section: Introductionsupporting
confidence: 90%
“…Much more work has gone into studying the health effects of fine particles because they have been linked to adverse human health effects (Dockery and Pope, 1994;Schwartz, 1994;EPA, 2009), and PMf often constitutes the largest fraction of PM 10 in urban areas (Stolzel et al, 2005;Stone et al, 2011;Kassomenos et al, 2012). More recently, adverse human health effects have been associated with the coarse particles (Castillejos et al, 2000;Mar et al, 2000;Lipsett et al, 2006;Graff et al, 2009), which has implications for more rural environments where the PMc mass fraction is often 50-70% of PM 10 (Ostro et al, 1999;Sprovieri and Pirrone, 2008;Sprovieri et al, 2011). The concern is even greater for the Pinal County area where the PMc mass fraction is often 80-90% of PM 10 (EPA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] This is due to a greater occurrence of natural aerosol sources in southern Italy during the springsummer seasons. 39,40 As reported in recent studies, 41-44 the highest PM 10 values recorded over the Mediterranean area occur during the warmer seasons, and are generally correlated with anticyclonic conditions [45][46][47][48][49][50] that favor the re-buildup of particles, particularly the advection of Saharan dust. 51,52 In the winter season, the typical meteorological conditions in the central Mediterranean basin are influenced by the presence of cyclones, the remixing of air masses and the reinforcement of winds.…”
Section: Resultsmentioning
confidence: 64%
“…Furthermore, particle composition and concentration are extremely changeable and depend on many factors such as climate variations, emission sources, and geographical position. Intriguingly, its composition may change on a daily basis and even during the same day (Cyrys et al, 2003;Chow et al, 2002;Osornio-Vargas et al, 2003;Rodríguez et al, 2004;Ariola et al, 2006;Becker et al, 2005;Sunder Raman et al, 2007;Bell et al, 2007a;Sprovieri and Pirrone, 2008;Perrino et al, 2008). A recent study in the Italian city of Genoa on the concentration and composition of the elements in the various fractions of PM (PM 10 , PM 2.5 and PM 1 ) has reported that the lightest elements are more concentrated in the fractions with a smaller diameter and that sulphur is the most relevant component in all fractions (Ariola et al, 2006).…”
Section: Introductionmentioning
confidence: 95%